2014
DOI: 10.1177/2167696814551786
|View full text |Cite
|
Sign up to set email alerts
|

“Dad Doesn’t Text”

Abstract: Advancements in technology have altered how and when communication occurs between individuals in a relationship. Although research has investigated how new information communication technologies (ICTs) affect peer relationships and parents' communication with their young children, how ICTs influence parent-adult child relationships is less clear. Based on media multiplexity theory (MMT), this study tested whether the number of media used to interact influences communication and relationship satisfaction for em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 34 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…Thanks to communication technologies, college students today have frequent interaction with parents via electronic channels (Miller-Ott, Kelly, & Duran, 2014; Schon, 2014) despite the physical distance. Frequent parent-child communication is associated with higher relational closeness (Miller-Ott et al, 2014) and relationship satisfaction (Schon, 2014) between college students and their parents. Among various social media, SNSs may stand out for their low intrusiveness and convenience in sharing life events.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to communication technologies, college students today have frequent interaction with parents via electronic channels (Miller-Ott, Kelly, & Duran, 2014; Schon, 2014) despite the physical distance. Frequent parent-child communication is associated with higher relational closeness (Miller-Ott et al, 2014) and relationship satisfaction (Schon, 2014) between college students and their parents. Among various social media, SNSs may stand out for their low intrusiveness and convenience in sharing life events.…”
Section: Introductionmentioning
confidence: 99%
“…However, only phone calls with parents were associated with the quality of the relationship. Schon (2014) found that although the number of tech-mediated modes used by parents and children to communicate with each other was associated positively with relationship satisfaction, relationship satisfaction was better explained by communication competence. Taken together, these findings suggest that tech-mediated communication may be a useful, albeit insufficient, tool for maintaining quality relationships.…”
Section: Tech-mediated Communication In Nonadoptive Familiesmentioning
confidence: 92%
“…Media multiplexity theory (MMT) emphasizes that individuals use many different channels to communicate; individuals in stronger relationships use more media to communicate (Haythornthwaite, 2005). Building on this perspective, Schon (2014) hypothesized, and concluded with modest effect sizes, that the number of channels used to communicate (i.e., "communication repertoire size") is positively associated with the quality of the parent-child relationship. For example, a mother and adolescent, with strong ties, will communicate over more channels (e.g., phone calls, FaceTime, texting) than the mother and adolescent with weaker ties, who may use only one or two channels with each other.…”
Section: Social Domain Theory and Communication Privacy Management Thmentioning
confidence: 99%